Sifat fisik, kimia, dan morfologik kulit jaket kambing tersamak menggunakan krom hasil recovery air limbah penyamakan - Sri Sutyasmi (Majalah Kulit, Karet, dan Plastik, 2015)
The purpose of this study was to recover chrome in tanning waste water to reduce environmental pollution and to utilize chrome as tanning agent. Chrome in tanning waste water leaching out of the drum was filtered and put in the tank and subsequently it was added with NaOH to generate chrome hydroxide. Furthermore, chrome hydroxide was converted to chrome sulfate as tanning agent by addition of concentred sulfuric acid. Cr2O3 content of chrome sulfate was determined before being used for tanning. The result showed that Cr2O3 content was 3958.6 mg/l. Variation of recovered chrome sulfate concentrations for tanning jacket leather were 25, 50, 75 and 100% respectively. Controls were made with the use of 100% of industrial grade chrome sulfate. The best result were goat jacket leather tanned with recovered chrome of 75 and 100 % for its physical properties and 25% for its chemical properties. Test results of SEM showed that chrome was morphologically presence in tanned goat leather mass.Keywords: tanning, jackets leather, chrome recovery, physical and chemical properties, leather morphology.ABSTRAKTujuan dari penelitian ini adalah mengambil kembali krom dalam air limbah penyamakan krom untuk mengurangi pencemaran lingkungan dan menghemat pembelian puder krom sebagai bahan penyamak krom. Air limbah penyamakan krom yang keluar dari drum, disaring dan dimasukkan dalam tangki dan ditambah NaOH untuk diendapkan menjadi krom hidroksida. Selanjutnya krom hidroksida dialirkan ke tangki yang lain dan ditambahkan asam sulfat pekat menjadi krom sulfat yang digunakan untuk menyamak. Hasil diuji kadar Cr2O3 terlebih dahulu sebelum digunakan untuk menyamak. Hasil uji kadar Cr2O3 adalah rata-rata sebesar 3958,6 mg/l. Variasi konsentrasi krom sulfat hasil recovery untuk penyamakan kulit jaket berturut-turut 25, 50, 75, dan 100%. Krom sulfat pasaran dengan konsentrasi 100% digunakan sebagai kontrol. Hasil uji sifat fisis kulit jaket kambing terbaik adalah konsentrasi krom berturut-turut 75 dan 100 % dan untuk sifat kimia kulit jaket terbaik 25 % yang disamak dengan krom sulfat hasil recovery. Hasil uji SEM menunjukkan bahwa secara morfologi krom dijumpai dalam kulit tersamak.Kata kunci: penyamakan, kulit jaket, chrome recovery, sifat fisik dan kimia, morfologi kulit.